Complete sequence analysis of two cryptic plasmids from Bifidobacterium kashiwanohense JCM 15439 (type strain) isolated from healthy infant feces. (19th July 2013) - Takahata, Muneaki; Toh, Hidehiro; Nakano, Akiyo; Takagi, Misako; Murakami, Masaru; Ishii, Yasuo; Takizawa, Tatsuya; Tanabe, Soichi; Morita, Hidetoshi
Abstract Bifidobacterial plasmids reported so far are derived from a limited number of strains and plasmids of bifidobacterial type strains isolated from humans are unknown. We found that Bifidobacterium kashiwanohense JCM 15439 (type strain) isolated from a healthy infant contained two cryptic plasmids, designated pBBKW‐1 and pBBKW‐2. We determined and analyzed the complete sequences of both plasmids. pBBKW‐1 (7716 bp) was predicted to replicate by a rolling‐circle mechanism and encode six protein‐coding genes, two of which are putative replication proteins. pBBKW‐1 seems to be a cointegrate plasmid containing two copies of the plasmid pMG1 from Bifidobacterium longum. pBBKW‐2 (2920 bp) was predicted to encode six protein‐coding genes and be a theta‐type replicating plasmid, which has been reported to be more stable than a rolling circle‐type replicating plasmid frequently found in bifidobacteria. Our finding will provide new insights into safe recombinant plasmid constructions for humans.